2008
DOI: 10.1002/ajhb.20765
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the relationship between leptin and adiposity among Tsimané children and adolescents

Abstract: Leptin is thought to signal energy stores, thus helping the body balance energy intake and expenditure. However, the strong relationship between leptin and adiposity in populations with adequate nutrition or common obesity is not universal across ecologic contexts, and leptin often correlates only weakly, or not at all, with adiposity in populations of lean or marginally-nourished males. To clarify whether the relationship between adiposity and leptin changes during development, this study examines leptin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Additionally, we did not explicitly include onset of puberty in our analyses. This may be an important factor to consider given that both adiponectin and leptin are suppressed by increased androgen release during puberty [46], [47]. However, data for our cohort show that child adiponectin, leptin and BMI did not yet differ by sex at 9 years (Table S1).…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, we did not explicitly include onset of puberty in our analyses. This may be an important factor to consider given that both adiponectin and leptin are suppressed by increased androgen release during puberty [46], [47]. However, data for our cohort show that child adiponectin, leptin and BMI did not yet differ by sex at 9 years (Table S1).…”
Section: Discussionmentioning
confidence: 79%
“…Adiposity increases with age, reaching Frisch's (Frisch and McArthur, 1974) ''critical fatness'' threshold of 22% by 15 years of age when leptin increases markedly. Boys, on the other hand, retain a fat level of about 10% and an extremely low leptin concentration throughout adolescence, suggesting that leptin is a more important signal of energy availability in females than in males in this population (Sharrock et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Weak correlations of leptin with adiposity in lean human males, in some marginally nourished populations, have raised questions about leptin's presumed role in the regulation of adiposity (Bribiescas, 2001;Kuzawa et al, 2007). For example, extremely low leptin levels have been reported for the Tsimané of lowland Bolivia (Sharrock et al, 2008). Leptin becomes increasingly coupled to fatness in girls in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin values, which correlate with the amount of body fat present, are reported to increase in girls and decrease in boys after Tanner stage 2 as the pubertal developments proceeds [ 24 ]. Another study conducted in 2- to 5-year-old Tsimané children showed that the correlation between body fat and leptin increases markedly with advancing age in females [ 25 ]. The lower levels of leptin in boys may partly be explained by the suppressive effect of androgens in the boys [ 24 ].…”
Section: Discussionmentioning
confidence: 99%